Sosialisasi Penggunaan Canva Dalam Pembuatan Media Promosi Kesehatan di Masyarakat - harsiwi, tria; Isabella Rahmawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstract. In today's increasingly advanced digital era, digital media has become an effective means of conveying information to the public. Canva is an online design program that provides various services such as presentations, resumes, posters, flyers, brochures, graphics, info graphics, banners, bookmarks, newsletters, and others. The method of community service carried out is by conducting outreach or presenting material regarding the use of Canva as a media for promotion and health information in the community. This outreach was carried out to the community, especially cadres and young people in the Ngebel Tamantirto community. Community service related to the use of the Canva application as a health promotion medium in the community is running well and smoothly. It is hoped that with this outreach, the public can utilize Canva in creating information media and health promotion in the community Keywords: Sosialization, Canva, Health Promotion